2020
DOI: 10.1111/jocs.15017
|View full text |Cite
|
Sign up to set email alerts
|

Time of day does not influence outcomes in acute type A aortic dissection: Results from the IRAD

Abstract: Background: Type A acute aortic dissection (TAAAD) represents a surgical emergency requiring intervention regardless of time of day. Whether such a "evening effect" exists regarding outcomes for TAAAD has not been previously studied using a large registry data. Methods: Patients with TAAAD were identified from the International Registry of Acute Aortic Dissections (1996-2019). Outcomes were compared between patients undergoing operative repair during the daytime (D), defined as 8 am-5 pm, versus the evening (N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 24 publications
3
26
0
Order By: Relevance
“…In overall, we agree with Arnaoutakis et al 1 that ATAAD is a surgical emergency, and decision for surgery should be based on clinical condition; however, a dedicated aortic team and experienced surgeons with larger volumes of ATAAD operations possibly contributed to these equivocal outcomes regardless of the time of the day.…”
Section: Time Of the Day Or Surgeon Volume-experience Matters Most?supporting
confidence: 87%
See 1 more Smart Citation
“…In overall, we agree with Arnaoutakis et al 1 that ATAAD is a surgical emergency, and decision for surgery should be based on clinical condition; however, a dedicated aortic team and experienced surgeons with larger volumes of ATAAD operations possibly contributed to these equivocal outcomes regardless of the time of the day.…”
Section: Time Of the Day Or Surgeon Volume-experience Matters Most?supporting
confidence: 87%
“…We read with great interest the study by Arnaoutakis et al, 1 They concluded that there was no difference in mortality between the two groups.…”
Section: Time Of the Day Or Surgeon Volume-experience Matters Most?mentioning
confidence: 93%
“…As such, in reality, it is possible that there is no mortality difference for OOH versus IH. This coheres with a recent International Registry for Acute Aortic Dissection study, which found no difference for mortality based upon the time of day of the operation 20 . Hence, a word of cautious optimism: while much work remains for improving outcomes after ATAAD surgery, OOH surgery may not underperform, as compared to IH surgery.…”
supporting
confidence: 68%
“…Karadakhy and Harky for their thoughtful letter in reference to our study examining time of day and surgical outcomes for Type A dissection according to the IRAD registry. 1 The key findings of our study included a slight majority of patients undergoing surgery at night. There were no differences in operative mortality based on operative time of day, nor was there any evidence of different mortality outcomes for patients operated on during the weekend versus weekday.…”
Section: Time Of the Day Or Surgeon Volume-what Matters Most In Type mentioning
confidence: 99%